KONSTRUKSI METODOLOGIS DAN DIMENSI AKSIOLOGIS FIQH SOSIAL KH. SAHAL MAHFUDH DALAM KONDISI SOSIAL KONTEMPORER - Muchlis Bahar (AKSELERASI: Jurnal Ilmiah Nasional, 2020)
The purpose of this study was to analyze the methodological construction and axiological dimensions of KH Sahal Mahfudh's social fiqh in contemporary social conditions. This research uses qualitative research with theological and sociological approaches. The data used in this research is secondary data. Collecting data using library research method. Based on the results of data analysis, it can be concluded that the social fiqh construction of KH Sahal Mahfudh consists of six main aspects, namely the Contextuality of Fiqh Texts, Switching from the Qauli School (Textual Paradigm) to the Manhaji School (Methodological Paradigm), Verification of Usul and Furu', Fiqh as Social Ethics, Application of Philosophical Thought in Socio-Cultural Context and Ijtihad Jama'i. In analyzing the axiological aspects of the construction, there are several things, namely the concept of ijtihad jama'i which is applied in collaboration between the BPJPH, the Ministry of Home Affairs and the Indonesian Ulema Council in assisting the halal certification of SMEs in the field of product exports, in matters of prostitution adhering to the akhafudz al-dhararain rule, KH Sahal Mahfudh built and mobilized the surrounding community to build self-help groups, hospitals and banks to help improve the collective economy, and the idea of ​​contestual education.